Major histocompatibility complex class II antigen (HLA-DR) expression by ileal epithelial cells in patients with seronegative spondylarthropathy. Issue 5 (May 1990) - Cuvelier, C; Mielants, H; De Vos, M; Veys, E; Roels, H
Abstract : Major histocompatibility complex molecules act as non-specific receptors for antigenic proteins and present them to T-cells. Presented antigen together with class II molecules activates antigen specific T-helper cells and may trigger a cellular immune response. The expression of HLA-DR antigens by epithelial cells was examined with an indirect peroxidase technique in ileal biopsies from 38 patients with seronegative spondylarthropathy and features of acute or chronic gut inflammation on biopsy, 14 patients with chronic inflammatory bowel disease, 10 rheumatic and 10 non-rheumatic controls. In acute ileitis, there was more HLA-DR expression in villous and crypt epithelial cells than in non-inflamed controls (p less than 0.01). In chronic inflammation and in chronic inflammatory bowel disease, class II antigens were more expressed in villus (p less than 0.02) and crypt epithelium (p less than 0.01). Strong HLA-DR expression in crypt epithelial cells was connected with active inflammation (p less than 0.02). These findings suggest binding of unknown enterobacterial or nutritional luminal antigens to HLA-DR antigens normally present in enterocytes. The enterocytes act as antigen presenting cells causing a local increase of targets for activated T-cells and trigger the gut inflammation responsible for the clinical symptoms of the seronegative spondylarthropathy.